Comprehensive phenomic and genomic studies of the species, Pectobacterium cacticida and proposal for reclassification as Alcorniella cacticida comb. nov - Jonca, Joanna; Pirhonen, Minna; Waleron, Michal Mateusz; Gawor, Jan; Mrozik, Agnieszka; Smoktunowicz, Magdalena; Waleron, Krzysztof; Waleron, Malgorzata (Frontiers in Plant Science, 2024)
Pectobacterium cacticida is a causative agent of the soft rot disease of cacti. In this study, we present the whole genome sequences of five strains. We performed phylogenomic analyses, which revealed that the species form a separate lineage from the Pectobacterium genus. We evaluated the genomes for the presence of virulence determinants and genes responsible for the adaptation to different hosts and the environment. We discovered 516 proteins unique to the species, most of which were involved in cellular metabolism. They included genes of carbohydrate metabolism and transport and ABC transporters, possibly enhancing the species' survival and virulence. We correlated our findings with the biochemical and phenotypic assays. The main differing characteristics from other Pectobacterium species were the lack of a myo-inositol degradation pathway and the presence of the malonate decarboxylase gene. Additionally, we performed pathogenicity tests to affirm the species' virulence potential. All tested strains were pathogenic towards Opuntia spp., chicory, Chinese cabbage, and potato but exhibited only mild pathogenicity towards carrot. Based on the phylogenomic analyses, we propose the reclassification of P. cacticida to the new genus, Alcorniella comb. nov.